Improving the efficiency of the process of continuous flow mixing of bulk components - Shevchenko, Igor; Aliiev, Elchyn (Eastern-European Journal of Enterprise Technologies, 2020)
Modern industrial and agricultural processing almost always implies mixing loose material on a variety of equipment. At present, there are known mixers of various designs, principles, and techniques to implement the technological process. One of the existing mixing techniques is a continuous flow method that has significant advantages – reducing energy intensity while improving the quality of the process of the mixture continuous preparation and distribution. However, the continuous-flow technique of mixing loose materials has been paid little attention to. This prevents the application of well-known analytical models of the process of moving loose components to substantiate the structural and technological parameters for the working bodies of a continuous flow mixer. The result of the analytical study of the continuous-flow mixing technique is the constructed system of differential equations of the movement of a bulk material’s components in the airflow under the influence of the working bodies’ surfaces of the designed mixer. The reported system of differential equations underlies the physical-mathematical apparatus for the numerical modeling of the specified process employing the software package StarCCM+ (USA). The result of the numerical modeling is the established dependences of the dynamics of change in the concentration of components in the mixture and the homogeneity of the mixture in the zones of a continuous flow mixer depending on the study factors (the frequency of rotations, the angle of attack of the blade mixer, the performance of feeding the first and second components). The optimal structural and technological parameters for a continuous flow mixer involved in the process of mixing a two-component feed mixture (stem and concentrated feed) have been determined, at which the uniformity of the resulting forage mixture is maximal